Kinetic Spectrophotometric Determination of Copper in Food - Hu, Wei-Hua; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2012)
Copper is an important metallic element in nature. It is also one kind of important trace element for life body. The study and establishment of a method for the determination of copper has important significance. A new kinetic-spectrophotometric method is proposed for the determination of copper in present study. The method is based on the catalytic effect of copper(II) on the oxidation of dibromo-p-chloro-chlorophosphonazo (DBC-CPA) by hydrogen peroxide in 1 mol L-1 phosphoric acid medium. Copper can be spectrophotometrically determined by measuring the decrease in the absorbance of dibromo-p-chloro-chlorophosphonazo at the wavelength of 550 nm using the fixed-time method. The linear range of the present method is 0.1-2.0 μg in 10 mL of solution and the limit of detection is 9.05 ng mL-1. The method has been successfully applied to the determination of copper in apple and banana. The relative standard deviations of 13 determinations of the method were 0.82-1.03 %. The recoveries of the present method were 101.3-103.6 %.